Trade liberalization and wage inequality in the Philippines - Rana Hasan; Robert L. Jandoc (University of the Philippines, School of Economics (UPSE), 2010)
We examine the role of trade liberalization in accounting for increasing wage inequality in the Philippines from 1994 to 2000 - a period over which trade protection declined and inequality increased dramatically. Using the approach of Ferreira, Leite, and Wai-Poi (2007), we find that trade-induced effects on industry wage premia and industry-specific skill premia account for an economically insignificant increase in wage inequality. A more substantial role for trade liberalization comes through trade-induced employment reallocation effects whereby reductions in protection appear to have led to a shift of employment to more protected sectors, especially services where wage inequality tended to be high to begin with. Nevertheless, the key drivers of wage inequality appear to be changes in economy-wide returns to education and changes in industry membership over and above those accounted for by our estimates of trade-induced employment reallocation effects. In order for trade liberalization to account for a relatively large portion of the increases in wage inequality, it would have to be a major determinant of the changes in economy-wide returns to education.
Keywords: 330; Außenhandelsliberalisierung; Einkommensverteilung; Soziale Ungleichheit; Philippinen